VIRTUAL DISTRIBUTING STATION SEBAGAI SARANA MEDIA PEMROGRAMAN PLC - Badarudin, Rohjai (DPTE FT UNY, 2022)
ABSTRACTThis study aims to develop learning media Virtual Distributing Station for PLC programming. The development model adopts the water-fall procedure from Presman. The waterfall procedure includes 1) communication, 2) planning, 3) modeling, 4) construction, and 5) system delivery. Product validation is carried out by material experts, media experts, and early adopters. The research instrument used a questionnaire with a 4-point Likert scale. The results showed that the performance of the virtual distributing station was included in the Very Eligible category, the feasibility of the virtual distributing station was included in the Very Appropriate category according to material experts, media experts, and early user responses. Thus, the virtual distributing station is very feasible to be used as a PLC programming medium because (1) it has met the eligibility test criteria, (2) it is flexible, it can be installed on a large number of computers, (3) it can be operated based on PLC programming, (4) more economical, limited to PLC programming to operate distributing station.ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran Virtual Distributing Station untuk pemrograman PLC. Model pengembangan mengadopsi dari prosedur water-fall dari Presman. Prosedur water-fall meliputi 1) komunikasi, 2) perencanaan, 3) pemodelan, 4) konstruksi, dan 5) penyerahan sistem. Validasi produk dilakukan oleh ahli materi, ahli media, dan pengguna awal. Instrumen penelitian menggunakan angket dengan skala likert 4 poin. Hasil penelitian diketahui bahwa unjuk kerja virtual distributing station termasuk dalam kategori Sangat Layak, kelayakan virtual distributing station termasuk dalam kategori Sangat Layak menurut ahli materi, ahli media, dan respon pengguna awal. Dengan demikian virtual distributing station Sangat Layak untuk digunakan sebagai sarana media pemrograman PLC karena (1) telah memenuhi kriteria uji kelayakan, (2) fleksibel, bisa dipasang pada komputer dalam jumlah banyak, (3) dapat dioperasikan berbasis pemrograman PLC, (4) lebih ekonomis, sebatas pada pemrograman PLC untuk mengoperasikan distributing station.